2014
DOI: 10.1371/journal.pone.0088846
|View full text |Cite|
|
Sign up to set email alerts
|

A Palindromic CpG-Containing Phosphodiester Oligodeoxynucleotide as a Mucosal Adjuvant Stimulates Plasmacytoid Dendritic Cell-Mediated TH1 Immunity

Abstract: BackgroundCpG oligodeoxynucleotides (ODNs), resembling bacterial DNA, are currently tested in clinical trials as vaccine adjuvants. They have the nuclease-resistant phosphorothioate bond; the immune responses elicited differ according to the CpG ODN sequence and vaccination method. To develop a CpG ODN that can induce plasmacytoid dendritic cell (pDC)-mediated TH1 immunity through the mucosa, we constructed phosphodiester G9.1 comprising one palindromic CpG motif with unique polyguanosine-runs that allows degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…It has been reported that phosphodiester (PO)-bonded CpG-ODN, which does not require PS, exhibits strong immune activity due to the characteristics of its structure. 47 We therefore anticipate the development of PS-independent ODNs in the near future. The ability to compound capsules containing various ODN sequences opens the possibility of using ODNcaps in in vivo studies employing a variety of mouse disease models.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that phosphodiester (PO)-bonded CpG-ODN, which does not require PS, exhibits strong immune activity due to the characteristics of its structure. 47 We therefore anticipate the development of PS-independent ODNs in the near future. The ability to compound capsules containing various ODN sequences opens the possibility of using ODNcaps in in vivo studies employing a variety of mouse disease models.…”
Section: Discussionmentioning
confidence: 99%
“…G9.1 is a CpG‐ODN (oligodeoxynucleotides containing non‐methylated CpG motif) 48 . Nasally administered G9.1 and Dtd induced Dtd‐specific mucosal IgA and serum IgG responses with antitoxin activity in mice 48 . G9.1 also exhibited strong IFN‐α‐inducing activity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, GACGATCGTC with a 9-mer oligoG on the 5 0 side and a single G on the 3 0 side (GGGGGGGGG-GAC-GATCGTC-G) was found to be a potent inducer of IFN-a in human PBMCs. 26 We call this CpG ODN "G9.1. "…”
Section: Development Of Ifn-inducing Cpg Odnsmentioning
confidence: 99%
“…G9.1, even in its naked form, exhibits adjuvanticity during nasal vaccination in mice. 26 In those mice, an excess production of proinflammatory and immunosuppressive cytokines is not induced. Further, repetitive administration does not cause problems in the major organs, and IgE antibody (Ab) production is not induced but may be suppressed in a mouse model of ovalbumin-induced allergy.…”
Section: Suitability Of Po-palcpg As a Mucosal Adjuvantmentioning
confidence: 99%
See 1 more Smart Citation